Knowledge management in organizations : 12th International Conference, KMO 2017, Beijing, China, August 21-24, 2017, Proceedings /: 12th International Conference, KMO 2017, Beijing, China, August 21-24, 2017, Proceedings. ([2017]) - Unknown
No abstract available